The interaction of public-school teachers with student users of psychoactive substances - Rossi, Lilian Cristina Castro [UNESP]; Dalben, Ivete [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (My University, 2010)
The increasing and early use of psychoactive substances by children and adolescents represents a challenge to public-health practice. To understand teachers interactions with student users of drugs and develop a representative theoretical model of such experience this study was conducted. Qualitative study conducted in São Paulo, Brazil, with 32 teachers from public schools by means of focal groups and based on the Grounded Theory as its methodological framework. Progressively comprehensive categories converged to three phenomena: Identifying student s users; Feeling powerless in face the challenges of drugs use; Silencing to preserve oneself from a threatening scenario. These phenomena constructed the core category of the experience: Silencing to preserve oneself from a threatening scenario in face of the fragility of rescuing student s users of drugs. The clash between inducing and protective factors in the concrete situations of drugs use was revealed, thus pointing out that the lack of State and social support associated with the user s relation with drug trafficking and violence leads teachers to silence as they feel unprotected in face ofa situation surrounded by stigma and prejudice. Coping strategies should include the educators, relatives, health care professionals and government institutions, thus providing ways to prevent and treat use, orientate and reconstruct lives in a process of active participation for all students.

Одной из актуальных проблем общественного здравоохранения является значительное увеличение употре- бления психоактивных веществ среди детей и подростков. Цель данного исследования – рассмотреть взаимо- отношение учителей и учеников, употребляющих наркотические средства, и разработать теоретическую схему поведения на основе полученного опыта. Исследование проводилось в Сан-Паулу, Бразилия. 32 учителя об- щеобразовательных школ приняли участие в научном эксперименте. Три основные модели взаимоотношений были установлены: выявление студентов, употребляющих психоактивные вещества, безысходность в условиях сложившейся ситуации, молчание с целью уклонения от ужасающих последствий. Самой распространенной моделью поведения оказалась ситуация неразглашения информации с целью уклонения от малоприятных по- следствий в связи с моральной неготовностью учителей принять меры для оказания помощи рассматриваемой группе детей и подростков. Недостаточная поддержка со стороны государства и социальных сообществ при- водит к нелегальному распространению психоактивных веществ и жестокости, что, в свою очередь, ставит учителей общеобразовательных школ в условия безысходности и незащищенности. Совместная деятельность работников образования и здравоохранения, родственников детей и государственных учреждений позволит решить и в будущем предотвратить данную проблему.
Де Кастро Росси Л.К., Далбен И., Мангини Бокчи С.К. Проблема взаимодействия учителей общеобразователь-ных школ и студентов, употребляющих психоактивные вещества // Саратовский научно-медицинский журнал
Keywords: Qualitative research; Grounded theory; Disorders related to substance use; School children’s health; Adolescent; качественный анализ; основная теория; нарушения; связанные с употреблением психоактивных веществ; здо- ровье школьников; подросток